Formation And Historical Development of Inorganic Chemistry in Kimeni - I B Egamberdiev; E B Karshiev (Zien Journals, 2022)
The role of pedagogical technologies in teaching the use of modern inorganic materials in the acquisition of construction materials. The independence of the country is the basis for radical reforms in the field of national education for the purpose of further improving the effectiveness of the reforms, creating conditions for the comprehensive development of the state and society, modernization of the country and liberalization of all spheres of life. created. At present, large-scale reforms are being implemented in the education system of the country.
Keywords: Chemistry and its history; chemical thinking and its formation; chemical accumulation; the historical principle of teaching